Conjugated molecule based 2D perovskites for high-performance perovskite solar cells. Issue 38 (15th September 2021) - Zhu, Tao; Shen, Lening; Chen, Hanlin; Yang, Yongrui; Zheng, Luyao; Chen, Rui; Zheng, Jie; Wang, Junpeng; Gong, Xiong
Abstract : Perovskite solar cells formed from a 2D/3D bilayer perovskite thin film, where 2D perovskites were created by novel conjugated molecules, exhibited a power conversion efficiency of 21.98% and a dramatically boosted stability was demonstrated. Abstract : Conjugated molecules have been typically utilized as either hole or electron extraction layers to boost the device performance of perovskite solar cells (PSCs), formed from three-dimensional (3D) perovskites, due to their high charge carrier mobility and electrical conductivity. However, the passivating role of conjugated molecules in creating two-dimensional (2D) perovskites has rarely been reported. In this study, we report novel conjugated aniline 3-phenyl-2-propen-1-amine (PPA) based 2D perovskites and further demonstrate efficient and stable PSCs containing a (PPA) x (MAPbI3 )1− x /MAPbI3 bilayer thin film (where MA is CH3 NH3 + ). The (PPA) x (MAPbI3 )1− x /MAPbI3 bilayer thin film possesses superior crystallinity and passivated trap states, resulting in enhanced charge transport and suppressed charge carrier recombination compared to those of a 3D MAPbI3 thin film. As a result, PSCs containing the (PPA) x (MAPbI3 )1− x /MAPbI3 bilayer thin film exhibit a power conversion efficiency (PCE) of 21.98%, which is approximately a 25% enhancement compared to that of the MAPbI3 thin film. Moreover, un-encapsulated PSCs containing the (PPA) x (MAPbI3 )1− x /MAPbI3 bilayer thin film retain 50% of their initial PCE after 1200 hours in an ambient atmosphere (25 °C, and 30 ± 10 humidity), whereas PSCs with the 3D MAPbI3 thin film show significant degradation after 100 hours and a degradation of more than 50% of their original PCE after 500 hours. These results demonstrate that the incorporation of conjugated molecules as organic spacer cations to create 2D perovskites on top of 3D perovskites is an effective way to approach high-performance PSCs.